Low-volume high-intensity interval versus continuous endurance training: Effects on hematological and cardiorespiratory system adaptations in professional canoe polo athletes - Sheykhlouvand, M.; Gharaat, M.; Khalili, E.; Agha-Alinejad, H.; Rahmaninia, F.; Arazi, H. (The Journal of Strength and Conditioning Research, 2018)
The aim of this study was to compare the effect of 2 paddling-based high-intensity interval training (HIIT) and continuous endurance training (CET) on hematological, immunological, and cardiorespiratory adaptations in professional canoe polo athletes. A total of 21 male canoe polo athletes were randomly divided into 1 of 3 groups (N = 7): (a) HIIT with variable intensity (VIHIIT) (6 × 60 seconds at 100, 110, 120, 130, 130, 130, 120, 110, 100% vVO2peak from first to ninth session, respectively, 1:3 work to recovery ratio); (b) HIIT with variable volume (VVHIIT) (6, 7, 8, 9, 9, 9, 8, 7, 6 repetitions/session from first to ninth session, respectively) × 60 seconds at lowest velocity that elicited VO2peak (vVO2peak), 1:3 work to recovery ratio); and (c) the CET group performed 3 times × 60 minutes paddling sessions (75% vVO2peak) per week for 3 weeks. Significant increases in VO2peak (ml/kg/min) (VIHIIT = 7.6%, VVHIIT = 6.7%), ventilation (VE) at VO2peak (VIHIIT = 11.5%, VVHIIT = 15.2%), respiratory frequency (R f) at VO2peak (VVHIIT = 21.1%), VO2 at ventilatory threshold (VT) (VIHIIT = 10.5%, VVHIIT = 25.1%), VE at VT (VIHIIT = 12.4%, VVHIIT = 34.0%), tidal volume at VT (VIHIIT = 11.7%, VVHIIT = 33.3%), R f at VT (VIHIIT = 9.7%), VE/VO2 at VT (VVHIIT = 13.1%), VO2/heart rate (HR) at VT (VIHIIT = 12.9%, VVHIIT = 21.4%), and VE/HR at VT (VIHIIT = 7.8%, VVHIIT = 27.2%) were seen compared with pretraining. Training interventions resulted in significant increases in mean platelet volume (VIHIIT = 2.7%, VVHIIT = 1.9%), mean corpuscular hemoglobin concentration (CET = 3.3%), and significant decrease in red blood cell distribution width (VVHIIT = -4.3), and cell numbers of lymphocyte (CET = -27.1) compared with pretraining. This study demonstrated that paddling-based HIIT enhances aerobic capacity and respiratory makers, without negatively affecting the immune system over 3 weeks.